Effects of different toothpastes on the prevention of erosion in composite resin and glass ionomer cement enamel and dentin restorations (Journal of Applied Oral Science, 2021)
Objective:This study aimed to evaluate the effects of different toothpastes on the surface wear of enamel, dentin, composite resin (CR), and resin-modified glass ionomer cement (RMGIC), and to perform a topographic analysis of the surfaces, based on representative images generated by atomic force microscopy (AFM) after erosion-abrasion cycles. Methodology: One hundred and forty bovine incisors were collected and divided into two groups: 72 enamel and 72 dentin blocks (4×4 mm). Half of the specimens were restored with CR (Filtek Z350 XT) and the other half with RMGIC (Fuji II LC). Then, samples were submitted to a demineralization cycle (5 days, 4×2 min/day, 1% citric acid, pH 3.2) and exposed to three different toothpastes (2×15 s/day): without fluoride (WF, n=12), sodium fluoride-based (NaF, n=12), and stannous fluoride-based (SnF2, n=12). Surface wear, as well as restoration interfaces wear, were investigated by profilometry of the dental substrates and restorative materials. All representative surfaces underwent AFM analysis. Data were analyzed by two-way analysis of variance and Tukey’s tests (α=0.05). Results: NaF-based toothpaste caused the greater dentin surface wear (p<0.05). Toothpastes affected only enamel-restoration interfaces. AFM analysis showed precipitate formation in dentinal tubules caused by the use of fluoride toothpastes. Conclusions: NaF-based toothpastes had no protective effect on enamel adjacent to CR and RMGIC against erosion-abrasion challenges, nor on dentin adjacent to RMGIC material. SnF2-based toothpastes caused more damage to interfaces between enamel and RMGIC.